The Effectiveness of Innovation that Promoted Fall Prevention Behavior among Elderly - ศิริโสภณ, ณัฐกฤตา (Journal of The Royal Thai Army Nurses, 2018)
The quasi-experimental research aimed to study The effectiveness of innovation that promoted fall prevention behavior among elderly. It was used the one group pre-test and post-test Design among 400 elderly in Bangkok Province using simple random sampling. PRECEDE Frame work was used as a conceptual framework in this study. The experimental group was received 4-week of innovation that promoted fall prevention behavior developed by the researcher. Innovation used information technology augmented reality (AR) through wall-mounted media using via smartphones to promote awareness, physical exercise skills and reinforcement from closed person and public health person. Data were collected before and after the experiment by using the Questionnaires which were developed by researcher. There were consisting of 3 parts: (1) biosocial data, (2) predisposing factors, enabling factors, reinforcing factors, and (3) a fall prevention behaviors. Content validity of the questionnaires was verified by the 3 experts. The reliability of the second part and 3rd parts were 0.790, 0.732, 0.802, and 0.712 respectively. The Data were analyzed by using the percentage, mean, standard deviation, and dependent samples t-test The results of the study showed that after participating in the Promoting Fall Prevention Behavior Innovation, the experimental group had higher mean scores on a fall prevention behavior than the baseline at a .05 statistical significance level.